Factors Affecting Buying Decision On Voluntary Social Insurance in Vinh Long City in Vinh Long Province, Viet Nam - Thanh Loan, Mai; Nguyen Hoang Truc Quyen, and (British Journal of Marketing Studies, 2020)
This study aims to examine the factors affecting purchase decision on voluntary social insurance of people in Vinh Long City, Vinh Long Province, Vietnam. The sample data of 370 survey responses was collected and stratified by age group. The regression analysis results shows five factors at the level of 0.05 sigificane. These are: Financial Benefits, Social Security Awareness, Influence of Relatives, Insurance Agents Staff and Income Awareness